Impact of Sett Disinfectants on Yellow Leaf Disease (YLD) Incidence and Yield and Growth Parameters in Sugarcane - Madugula, Suresh; Devi, G. Uma; Adilakshmi, D.; Kumar, N. Raja; Vijayalakshmi, K.; Bharatalakshmi, M.; Reddy, B. V. Bhaskara (International Journal of Bio-resource and Stress Management, 2023)
Yellow leaf disease (YLD) of sugarcane caused by sugarcane yellow leaf virus (SCYLV), a Polerovirus of the Luteoviridae family is becoming a major threat to sugarcane cultivation in north coastal region of Andhra Pradesh state. As YLD is mainly transmitted through sett borne inoculum, the present study was carried out to evaluate the efficacy of some disinfectants on the reduction of inoculum load through sett treatment and confirmed by DAS-ELISA. Further, their impact on cane growth, yield and juice quality parameters were observed. From the present study it was found that even though there was slight increase in the number of clumps with TSP treatment at various doses compared to infected canes it was not significantly different from the other disinfectant chemicals and healthy canes proved to more effective in reducing the incidence levels than the sett treatments. Further, healthy canes resulted in lowest disease incidence compared to all the sett disinfection treatments which were significantly at par with each other. Present study also revealed that the sett disinfection chemicals did not have any effect on the yield and juice quality parameters of sugarcane. Whereas, healthy canes proved as the best management option for YLD with reduced disease incidence resulting in increased number of millable canes (NMC) and cane yields with higher juice quality values, especially in ratoon, emphasizing the role of healthy planting material for the effective management of YLD in field conditions.